Kepemilikan Fasilitas Sanitasi Dasar Rumah Tangga Di Desa Air Selumar Kecamatan Sijuk Kabupaten Belitung - Dyah Suryani (Universitas Wiralodra, 2021)
Ownership of basic sanitation facilities of the house is one of the conditions of a healthy home. Health problems in the home environment can not be separated from the level of knowledge, attitude, income of the head of the family and the number of dependents of the head of the family. It is seen that there are still people who do not have thoughts about the importance of basic sanitation for their lives and there are still many people who do not have basic sanitation facilities. The purpose of this study is to find out the factors related to the ownership of basic household sanitation facilities in Selumar Water Village, Sijuk Subdistrict, Belitung Regency.This study uses observational analytics method with cross sectional approach. The samples in this study numbered 101 samples, using proportional random sampling method. Research instruments are questionnaires and checklists. Data analysis is performed using Chi square test. Bivariate analysis results show there is a relationship between the level of knowledge and the ownership of basic household sanitation facilities p value=0.000, there is a relationship between attitude with the ownership of basic household sanitation facilities p value=0.005, there is a relationship between the level of income and the ownership of basic household sanitation facilities p value=0.000, there is a relationship between the number of family members and the ownership of basic household sanitation facilities p value=0.016. The level of knowledge, attitude, income level and number of family members relates to the ownership of basic household sanitation facilities in Selumar Water Village, Sijuk Subdistrict, Belitung Regency